Determining the Hypothetical Hydrostatic Free Surface of the Closed Tank Filled Fully with Fluid Moving with an Acceleration to Calculate the Force Acting on Its Wall Applied in Fluid Transport - Luong, Ngoc Loi (Old Journal, 2020)
The hypothetical hydrostatic free surface is a new concept used to represent pressure distribution, calculate the pressure exerted on the wall of a moving closed tank with acceleration, translation or rotation around a fixed axis. The paper presents a common fluid mechanical problem, which has specific applications in liquid transport practice. The solution using the hypothetical hydrostatic free surface for a closed vessel is argued on the basis of mechanical theory. The article cited several new solutions and showed numerical examples to clearly see the results and assess more accurately the harmful effects of increasing pressure when the liquid transport vehicle suddenly accelerates, brakes especially in traffic crashes.